Documentation and evaluation of medicinal plants with potential for breast cancer therapy as used by Jakun Community of Kampung Peta, Mersing, Johor - Mainasara, Muhammad Murtala (2019)
Breast cancer (BC) is the most commonly diagnosed cancer and the leading cause of cancer-related death among women globally. Traditional knowledge (TK) could be a means for the development of new BC treatment; however, TK is perishing due to socialisation and lack of natural resources conservation. The research aimed to document the TK of medicinal plants used for the treatment of breast cancer by Jakun community of Kampung Peta, Mersing Johor; to examine the secondary metabolites, the antioxidant and cytotoxic effect of the selected plants extract. Documentation of TK was analysed qualitatively from semi-structured interviews. The six species (Artocarpus. altilis, Dioscorea bulbifera, Morinda citrifolia, Pinanga limosa, Ipomoea aquatica and Dianella ensifolia) from six families and six genera were documented. They were evaluated for their antioxidant properties using FRAP, ABTS and DPPH assays and the effects of the plant's extracts on the proliferation of MCF-7 and MDA-MB-231 cell lines were evaluated using MTT assay, cell cycle arrest and apoptosis. GC-MS was used to identify active the compounds. Findings showed that A. altilis have the highest antioxidant capacity and M. citrifolia, the least. A. altilis methanol extract (AAM), D. bulbifera methanol extract (DBM) and P. limosa methanol extract (PIM) were found to induce cytotoxicity against MCF-7 and MDA-MB-231 with the IC50 value range of 3.27 - 41.70μg/ml. Cell cycle analysis showed that the plant's extracts induced significant arrest at Sub G1 and G2/M at 24 hrs of treatment. Afterwards, 48 and 72 hrs of treatment, the proportion of cells in other phases had reduced significantly as compared to their control. Apoptosis occurred during the first 24 hrs and increased dramatically after 48 and 72 hrs of treatment. The GC-MS analysis revealed the presence of phytol, acetic acid and hexadecanoic acid among the major metabolites that might contribute to the anti-proliferative effect. The studies scientifically justified the use of the selected medicinal plant species by Jakun people. Further studies are necessary for detailed chemical characterisation and broader biological evaluation of the most active ingredients.